answersLogoWhite

0


Best Answer

The given terms can be simplified to: a -b

User Avatar

Wiki User

โˆ™ 2017-09-14 14:58:21
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
User Avatar

Zin Sabsaoub

Lvl 1
โˆ™ 2021-09-06 20:30:28
Good
User Avatar

Zin Sabsaoub

Lvl 1
โˆ™ 2021-09-06 20:30:44
BFD
More answers
User Avatar

Luca Desage

Lvl 2
โˆ™ 2020-11-04 16:38:39

Hh

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-13 17:08:07

2ab

User Avatar
User Avatar

Luca Desage

Lvl 1
โˆ™ 2020-11-04 16:38:20
Ok

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-10 14:23:36

2

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-11 14:32:10

89

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-11 19:51:02

Ghuy

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-13 13:20:54

10a -

User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-09-15 19:58:19

1b

User Avatar

Add your answer:

Earn +20 pts
Q: What is 9a plus 2b - 8a -3b?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

9a 3b take away 8a - 3b?

1a


What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


What is 3a plus 4b plus 6a plus 3b in algebra?

9a + 7b *remember to look and understand the letters!*


What is 9a minus 8a simplified?

9a - 8a = a


Can 9a - 3b plus c be simplified?

12


What is the vaule of 9a plus 3b?

3(3a+b)


What are the values of a and b if 6 3 is the midpoint of the line joining 2a comma 2a-b to a-2b comma 4a plus 3b?

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3


Solve the equation 9a-a equals 19 plus 7a?

9a-a = 19+7a 8a = 19+7a 8a - 7a = 19 + 7a - 7a 1a = 19 a = 19


What is a if 9a equals 18b?

If: 9a = 18b Then: a = 2b


What is the value of 9a 3b?

13


What is the equivalent to 3a plus 4b - -6a - 3b?

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b


2a plus 5a plus 9a equals?

2a+5a+9a = 16a


How do you factor 81a2 plus 36a plus 4?

(9a + 2)(9a + 2)


What is 12a plus 6b plus 9a plus 14b equals?

12a + 6b + 9a + 14b =(12a + 9a) + (6b + 14b) =21a + 20b


What is the factor of a2 plus 9a plus 20?

a2+9a+20 = (a+4)(a+5) when factored


What is 9a plus 21 equals?

9a+21 3(3a+7)


What is the answer to 9a plus 5?

There is nothing you can do to 9a + 5 without knowing the value of a.


-9(a plus b)?

The simplified expression is -9a -9b.


What is 9a plus 45z?

That cannot be simplified any further so it is: 9a + 45z


Simplify 7a plus 2a plus 1?

9a + 1


-14 plus 9a equals 38?

-14 + 9a = 389a = 52a = 52/9 or 5.78


What is the answer to 2 plus 3A plus 9A?

2 + 3A + 9A = 2 + 12AThe numerical value depends on the value of 'A'.It changes whenever 'A' changes.


What is 9a plus 8-2a-3-5a?

9a +8 -2a -3 -5a = 2a +5


How do you solve 1.5a plus 6 equals 9a plus 12?

a= -0.8


9a plus 15 equals 7a plus 9?

Collect like terms: 9a -7a = 9 - 15, ie 2a = -6, so a = -3